2021
DOI: 10.1016/j.jbc.2021.100835
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion of excess iron in mice requires hepatocyte iron import by Slc39a14

Abstract: Iron is essential for erythropoiesis and other biological processes, but is toxic in excess. Dietary absorption of iron is a highly regulated process and is a major determinant of body iron levels. Iron excretion, however, is considered a passive, unregulated process, and the underlying pathways are unknown. Here we investigated the role of metal transporters SLC39A14 and SLC30A10 in biliary iron excretion. While SLC39A14 imports manganese into the liver and other organs under physiological conditions, it impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…9,10 Physiologically, most of the iron that leaves the body is lost through menstruation in women or sloughing of epithelial-lined surfaces such as the skin, intestinal mucosa, urinary and biliary tracts. [11][12][13] There are no known regulated pathways for active iron excretion; therefore, maintaining systemic and intracellular iron homeostasis is largely dependent on absorption. 14…”
Section: Intestinal Absorption Of Ironmentioning
confidence: 99%
“…9,10 Physiologically, most of the iron that leaves the body is lost through menstruation in women or sloughing of epithelial-lined surfaces such as the skin, intestinal mucosa, urinary and biliary tracts. [11][12][13] There are no known regulated pathways for active iron excretion; therefore, maintaining systemic and intracellular iron homeostasis is largely dependent on absorption. 14…”
Section: Intestinal Absorption Of Ironmentioning
confidence: 99%
“…Since SLC39A14 and SLC39A8 are metal importers with a broader substrate specificity compared with SLC30A10, these studies are expected to provide insights beyond Mn excretion and into areas such as the transport of Mn across the bloodbrain barrier (95), as well as into neurons and glia, homeostatic control of other metals (e.g., SLC39A14 was recently reported to play a role in biliary excretion of excess iron; Ref. 96), and biology of other disease conditions (e.g., association of SLC39A8 missense mutation with Crohn's disease; Ref. 97).…”
Section: Emerging Directions For Future Investigationsmentioning
confidence: 99%
“…In contrast to all other minerals, iron cannot be actively regulated to be excreted from the body. While recent studies have documented biliary excretion of iron in genetically iron loaded knockout mice models (Mercadante et al, 2019; Prajapati et al, 2021), that has not been demonstrated as an active mechanism of iron regulation in other species, especially non‐iron loaded species such as the horse. The level of iron in the body is primarily regulated via absorption in the small intestine at the brush‐border membrane of duodenal enterocytes.…”
Section: Discussionmentioning
confidence: 99%